The grasscutter: an African delicacy - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
The grasscutter (Thyronomys swinderianus) is found throughout the African continent south of the Sahara. Several countries incorrectly attribute the name 'agouti' to it, arid it has several dialect names: 'kibondo' in Kiswahili, 'simbiliki' in...